2022
DOI: 10.1002/er.8322
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the prospects for future hydrogen storage in materials‐application and outstanding issues

Abstract: The ongoing population explosion has led to the rapid consumption of different energy sources. The continuous demand for energy and its associated services for socio-economic development is concerning due to the reduction of natural energy sources. Therefore, research to explore clean and sustainable energy sources to fulfill this energy demand has continuously been conducted over the past decades. Hydrogen is widely accepted as a possible energy carrier owing to its advantages, such as ease of availability, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 133 publications
0
17
0
Order By: Relevance
“…So alternative materials are constantly being explored and characterized by their ability to adsorb/absorb hydrogen. They are mainly found as hydrides [17], porous materials [18], and carbon nanomaterials [19] which we will discuss briefly. Hydrogen absorbing materials and its container to store H2 for application purposes are called solid-state hydrogen storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…So alternative materials are constantly being explored and characterized by their ability to adsorb/absorb hydrogen. They are mainly found as hydrides [17], porous materials [18], and carbon nanomaterials [19] which we will discuss briefly. Hydrogen absorbing materials and its container to store H2 for application purposes are called solid-state hydrogen storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…where the proportionality coefficient K is dened as shown in eqn (6), v is the gas volume under STP conditions (22.4 cm 3 mmol −1 of gas), M w,hyd is the molecular weight (g mol −1 ) of sII clathrate hydrate considering the thermodynamic promoter used in this study (THF) and is calculated as shown in eqn (7), n wh is the mole of H 2 O per mole of sII clathrate hydrate (i.e. 136), and r hyd (g cm −3 ) is the hydrate density, calculated using eqn (8), with A the Avogadro constant (6.023 × 10 23 mol −1 ) 68 and l the sII hydrate lattice parameter which is 17.145 Å when THF is used as a promoter and pressurized with H 2 gas in the bulk.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…Due to its very low density of approximately 0.089 kg/m 3 , hydrogen needs to be stored at high pressures. Currently, pressures of 25-35 MPa are used for storage (for fuel cell applications) and transport, and they can reach 70 MPa [81,82]. However, as pressure increases, this hydrogen compression process consumes excessive energy, leading to an increase in overall system cost [83].…”
Section: Compressed-gas Hydrogen Storagementioning
confidence: 99%